Liberdade - Castanhato, Camila (2013)
The Law is a conjectural science that must be studied in association with other areas of knowledge. Freedom, the study subject of this PhD thesis, has always been pillar of Law and predilection for philosophy. In this research, further the Philosophy of Law, in association with the Philosophy in Law. Therefore, this work brings, at first, the problem involving the freedom in our times, and methodological postulates that form this thesis: the Jus-normative humanism and the Humanist Capitalism with the strengthening of the Theory Imaginary of Law (and of Totality). Later we shall make an analysis about the variations of the concept of freedom in Western History. We shall see that the concept of freedom is absolutely inseparable from the world view in which it is inserted, and it is closely related to the political-economic system which arises in each historical period. In the Homeric universe, freedom is a purely political attribute assigned to only a tiny portion of the population - citizens, in the Christian universe, freedom translates itself in free will, while in the Newtonian universe, freedom is merely formal. The new concept of Freedom that we propose in this thesis takes as postulates the great ladies of Greek Mythology - Aphrodite, Themis, Athens and Demeter - that is, a concept of freedom that comes from the beautiful, the just, the wise and fruitful to formulate a Freedom of conscience of the coexistence, within a quantum view, either imaginary of the world, in a systematic legal and economic guided by the ideals of Humanist Capitalism. We believe that Law should be an instrument of realization of love and not a mere instrument of domination of man and the planet by man. This thesis was written in this spirit!